Studi tentang Perilaku Konsumen pada Rumah Makan Artis Ternama melalui Pendekatan Bauran Pemasaran - Didit Darmawan; Nurul Agustin (Pascasarjana STIE Amkop Makassar, 2026)
This study analyzes the influence of price, promotion, product variety, and location on visit intention to restaurants owned by celebrities. Data were collected from 100 respondents in Surabaya who had visited celebrity-owned restaurants, selected through purposive sampling technique. Multiple linear regression analysis was employed to test the hypotheses regarding the relationship between the independent variables and the dependent variable. The analysis reveals that each variable significantly shapes consumer visit intention through distinct mechanisms. Price functions as a value signal and market segmentation tool, while promotion builds awareness and transfers the celebrity's positive image to the culinary business. Product variety provides substantive reasons for visits and return visits through continuous innovation and quality consistency. Location determines accessibility and visibility, contributing to consumers' perceived convenience and safety. The uniqueness of celebrity-owned restaurants lies in the interaction between these four marketing variables and the affective factor of emotional attachment consumers have toward the public figure. This emotional attachment can amplify the attractiveness of each variable but simultaneously raises consumer expectations, demanding higher management standards. Celebrity popularity serves merely as an initial entry point, while sustainable visit intention requires professional, consistent, and integrated management of these fundamental marketing elements. The study offers theoretical contributions to consumer behavior literature and practical implications for restaurant managers and celebrity business owners.Keywords: price, promotion, product variety, location, visit intention, celebrity restaurant, consumer behavior